Thermal behaviour and polymorphism of BIMEVOX oxide ion conductors including the new materials: Bi4V2O11: M; M = La, Y, Mg, B - Lee, C.K.; West, A.R. (Elsevier, 1996)
The BIMEVOX materials can be prepared in four polymorphic modifications: α,β,γ,γ′, depending on Bi: V ratio and the nature/concentration of dopant. Polymorphic transitions take place on heat/cool cycles and can be detected by DTA and by variations in conductivity Arrhenius plots. A survey of thermal behaviour is given, using as examples several new BIMEVOX materials. Some conductivity values at 300 °C are: